A method for preparing micron-grade titanium alloy product
Through the combination of powder microinjection forming technology and a high flow binder system, the material limitations and processing difficulty of preparing micron-scale titanium alloy products in the prior art are solved, and the preparation of micron-scale titanium alloy parts with high density and excellent mechanical properties is achieved, with the advantages of low production cost and easy mass production.
Patent Information
- Application Number
- CN202111362708.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-17
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2041-11-17
AI Technical Summary
The prior art is difficult to effectively prepare high-quality micro-scale titanium alloy products, and there are problems of material limitations and difficult processing.
The micro-injection forming technology is used, combined with powder grading technology and a high flow adhesive system, micro-scale titanium alloy parts with high dimensional accuracy and excellent mechanical properties are prepared.
It achieves high density, excellent mechanical properties and low production costs, can match the performance of cast titanium alloys, and is easy to achieve mass production.
Smart Images

Figure CN114042917B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a titanium alloy product, in particular to a method for preparing a micron-grade titanium alloy product. Background Art
[0002] Entering the 21st century, people's requirements for lightweight products are growing. A series of microsystem technologies have emerged and are showing an increasingly important position. With the continuous expansion of the field of microstructures, more microstructures will be needed to meet the requirements of performance and large-scale production. Traditional processing technology is obviously incapable of such microstructure parts. Although existing advanced silicon etching technology, quartz crystal deep groove wet etching technology, special micromachining technology (micro-electrodischarge machining, micro-laser forming machining, micro-machining, etc.) and other processing technologies can produce micro parts that meet the requirements of use, they are expensive and have material limitations. Powder micro injection molding (uPIM) technology is to organically apply powder injection molding (PIM) technology to the preparation of devices with micron-level dimensions, and can meet the requirements of high cost performance, thus becoming the most promising new technology for the preparation of micro components. From the basic process point of view, uPIM and PIM are the same. Due to the micro characteristics of the product, uPIM technology has put forward more stringent requirements in terms of forming process and forming equipment compared with traditional PIM technology, such as powder selection, binder formulation, degreasing and sintering process parameters, etc.
[0003] Titanium and titanium alloys have the advantages of low density, high specific strength, non-magnetic, corrosion resistance and good biocompatibility. They are high-quality metal structural materials and functional materials. They have been widely used in aerospace, automobile, power generation, biomedicine and other fields. They are known as the "third metal" and "strategic metal" in development after steel and aluminum. However, titanium and titanium alloys have high melting points and hardness, and poor processing, molding and cutting performance. Therefore, the application value of using uPIM technology to prepare titanium and titanium alloy micro parts is more prominent. At present, most of the research on microinjection molding technology focuses on binder preparation and ceramic and other material systems. Yin Haiqing of Beijing University of Science and Technology disclosed a method for preparing a thermoplastic binder for powder microinjection molding. The composition of the binder is 5~40%PW+5~20%BW+10~32%HDPE+10~40%EVA+5~25%SA, and the content of each component is mass percentage (CN102775673A). Song Jinshuai of Haijingke Powder Metallurgy Technology Co., Ltd. disclosed a water-soluble binder for powder microinjection molding and a preparation method. In a constant temperature device, first completely melt the low-melting-point polyethylene glycol, then add the weighed ethylene-vinyl acetate and stearic acid and stir continuously, finally add polyvinyl butyral in batches and stir vigorously until a uniform emulsion is obtained, and then take it out after cooling to obtain the finished binder; the mass fraction of each component in the binder is: 20-40% of polyethylene glycol with a molecular weight of 1000-2000, 20-40% of ethylene-vinyl acetate, 20-40% of polyvinyl butyral, and 5-10% of stearic acid (CN106589562A). These binder systems all have defects to varying degrees. Although the wax-based system has good fluidity, the solvent degreasing efficiency is low and the carbon content of the resulting product is high. The water-based system is not strong enough and is prone to increase the oxygen content in the product. The performance of titanium alloys is greatly affected by impurity content such as carbon and oxygen. Once the interstitial impurity content is not properly controlled, the product quality will be out of control and waste will be caused. When the product has micro features, the degree of such influence will increase significantly. Lu Zhen from Harbin Institute of Technology provided a micro-injection molding method for a print head ceramic substrate. The specific steps are: selecting ceramic powder, preparing binder, preparing feed, microinjection molding, adding the prepared feed to the microinjection molding machine to form an injection blank, heating the temperature of the microinjection molding machine barrel to 180~240℃, heating the temperature of the nozzle to 175~240℃, and the microinjection pressure to 30~100MPa; thermal degreasing and pre-sintering, sintering, placing the molded blank in a high-temperature sintering furnace and sintering in an air atmosphere to obtain a ceramic substrate, the sintering temperature is 1400~2200℃, and the heat preservation is 1~3 hours; post-processing process, grinding and polishing the ceramic substrate (CN 101691086A). In summary, there is no report on uPIM related technology for titanium alloys. Summary of the invention
[0004] In order to solve the deficiencies in the prior art, the present invention provides a method for preparing micron-grade titanium alloy products. Based on powder micro-injection molding, powder grading technology is combined with a high-fluidity binder system for the first time to prepare micron-grade titanium alloy parts with high dimensional accuracy and excellent mechanical properties. The method has the advantages of low production cost and easy mass production.
[0005] The invention discloses a method for preparing a micron-grade titanium alloy product, comprising the following steps: firstly, mixing and granulating titanium alloy powder and a binder to obtain a feed material; then, obtaining a green body in a microinjection molding machine; and finally, sequentially performing thermal degreasing and sintering densification on the green body to obtain a titanium alloy product.
[0006] The titanium alloy powder is a mixture of coarse powder and fine powder, the average particle size of the coarse powder is 15-30um, the average particle size of the fine powder is 2-5um, and the mass percentage of the fine powder is 10-20%;
[0007] The binder is composed of the following components by mass percentage: 65-75% polyacrylonitrile, 10-20% ethylene-vinyl acetate copolymer, 10-20% high-density polyethylene, and 1-5% stearic acid;
[0008] The sintering process is any one of pressure sintering, hot isostatic pressing sintering and plasma discharge sintering.
[0009] As a preferred embodiment, the present invention provides a method for preparing a micron-sized titanium alloy product, wherein the titanium alloy powder is prepared by one of inert gas atomization, plasma beam rotating electrode atomization and electrode induction melting gas atomization.
[0010] As a preferred embodiment, in the method for preparing a micron-grade titanium alloy product of the present invention, the grade of the titanium alloy powder is any one of TC4, TC9, TC11, and TC21.
[0011] As a preferred embodiment, the present invention provides a method for preparing a micron-grade titanium alloy product, wherein during the mixing, the mixing temperature is 150-200° C., the mixing time is 1-4 hours, and the mixer speed is 80-120 r / min.
[0012] As a preferred embodiment, in the method for preparing a micron-grade titanium alloy product of the present invention, in the feed, the volume ratio of binder to powder is 30-40%:60-70%.
[0013] As a preferred embodiment, the present invention provides a method for preparing a micron-grade titanium alloy product, wherein during the injection, the injection temperature is 150-180°C, the injection pressure is 90-150MPa, and the mold temperature is 40-60°C.
[0014] As a preferred embodiment, the present invention provides a method for preparing a micron-grade titanium alloy product, wherein the thermal degreasing process is: under the protection of an argon atmosphere, first heating to 300-450°C at a heating rate of 1-3°C / min and keeping warm for 1-4 hours, then heating to 500-600°C at a heating rate of 1-3°C / min and keeping warm for 1-4 hours, and then cooling to room temperature with the furnace.
[0015] As a preferred embodiment, the present invention provides a method for preparing a micron-grade titanium alloy product, wherein the protective atmosphere for pressure sintering is argon, the sintering temperature is 800~1000°C, the holding time is 1~2h, the holding pressure is 100~300MPa, and the heating rate is 10~20°C / min; the protective atmosphere for hot isostatic pressing sintering is argon, the sintering temperature is 900~1000°C, the holding time is 0.5~1h, the holding pressure is 100~300MPa, and the heating rate is 100~300°C / min; the protective atmosphere for plasma discharge sintering is argon, the sintering temperature is 800~900°C, the holding time is 20~40min, the holding pressure is 50~150MPa, and the heating rate is 100~300°C / min.
[0016] As a preferred embodiment, the present invention provides a method for preparing a micron-sized titanium alloy product, wherein the maximum size of the titanium alloy product is no greater than 500 um.
[0017] As a preferred embodiment, the present invention provides a method for preparing a micron-grade titanium alloy product, wherein the oxygen content of the obtained titanium alloy product is not greater than 0.25wt.%, the tensile strength is not less than 835MPa, the yield strength is not less than 765MPa, the elongation is not less than 5%, and the dimensional accuracy is ±0.3~0.5%.
[0018] Principles and advantages
[0019] The present invention is based on powder microinjection molding technology. First, titanium alloy powder and binder are mixed and granulated to obtain feed; then a green body is obtained in a microinjection molding machine; finally, the green body is thermally degreased and sintered to obtain a titanium alloy product. Powder microinjection molding is the same as conventional powder injection molding process, but due to the micro characteristics of the product, uPIM technology has more stringent requirements than traditional PIM technology in terms of process, equipment, etc. Therefore, uPIM technology for titanium alloys needs to be studied one by one from the aspects of powder selection, binder preparation, injection process, degreasing process and sintering process.
[0020] The selection of powder plays a key role in the entire uPIM process. The average particle size of the powder used in uPIM is generally less than 3um, and the average particle size of many ceramic powders reaches less than 1um. At the same time, the better the sphericity of the powder, the better the shape accuracy and surface quality of the product. However, unlike stainless steel or ceramics, as the particle size decreases, the specific surface area increases, and the content of impurity elements will also increase accordingly, and the performance of titanium alloys is very sensitive to impurity elements. When the oxygen content exceeds 0.3wt.% or the carbon content exceeds 0.1wt.%, the elongation of the material is reduced to less than 2%, which cannot meet the application requirements as a functional structural material. Therefore, the present invention adopts a powder grading method, by effectively regulating the ratio of titanium alloy fine powder with an average particle size of 2~5um to titanium alloy coarse powder with an average particle size of 15~30um, it can not only avoid the increase of impurity content, but also ensure the size and accuracy requirements of the microstructure. At the same time, the use of inert gas atomization, plasma beam rotating electrode atomization or electrode induction melting gas atomization can be carried out in a completely inert atmosphere, thereby maintaining the high purity of the raw powder, and the powder obtained is spherical in shape with a wide particle size distribution and good stacking performance, thereby ensuring the surface quality of the product.
[0021] For injection molding, the composition of the binder is the key to material molding. Compared with conventional PIM molds, the wall thickness ratio of the flow channel to the cavity of the micro mold is larger, which requires the injection material of uPIM to have better fluidity to avoid premature solidification of the injection material during the injection process. On the other hand, for tiny injection parts with particularly complex shapes, they are required to be demolded completely and safely. If demolding fails, it will be very difficult to clean the core, and its complex and delicate microstructure is likely to be damaged. Therefore, the binder plays a very important role to balance and ensure the good fluidity of the injection material and the high strength of the injection part. The commonly used binder systems for PIM titanium alloys are wax-based systems, polyoxymethylene systems and water-based systems. Wax-based system binders occupy an important position in the PIM process, but their solvent degreasing efficiency is low and the carbon content of the resulting products is high, so their development is limited. For the polyoxymethylene system, during the injection process, polyoxymethylene may decompose to produce highly toxic formaldehyde, and the strong acid used in the catalytic degreasing process has a greater corrosive effect on the equipment, while increasing the time of subsequent thermal degreasing, and a surge in oxygen content may occur, so its large-scale production is limited. The strength of the water-based system is not enough, and it is easy to increase the oxygen content in the product. As mentioned above, the performance of titanium alloys is greatly affected by the impurity content, and when the product is miniaturized, the degree of such deterioration will increase significantly. Therefore, the present invention selects polyacrylonitrile with a low softening temperature (about 95°C) and good fluidity as a filler, high-density polyethylene and ethylene-vinyl acetate copolymer as a skeleton material to provide sufficient strength for the green body, and a small amount of stearic acid as a surface dispersant or activator, which can not only play a bridging role between the binder and the powder particles to prevent the two-phase separation and ensure uniform mixing, but also can play a lubricating role between the powder particles and between the powder particles and the mold wall. A new type of uPIM titanium alloy binder with high fluidity and high strength is obtained by adjusting the formula ratio.
[0022] The injection molding process refers to the process of injection molding the mixed material (feed material). The defects formed in this process cannot be eliminated in the subsequent process, so the process parameters must be strictly controlled. In the injection molding process, since the injection volume is very small each time and the heat dissipation is fast, the mold needs to be heated during injection, and the mold temperature should be able to drop rapidly after injection, because the high mold temperature will reduce the strength of the green body and further increase the difficulty of demolding. In addition to the mold temperature, factors such as injection temperature and injection pressure have a great influence on the microinjection process. When the injection temperature increases, the viscosity of the melt decreases, which is conducive to the filling of the plastic melt; when the injection temperature is kept at a high level, it is also conducive to the shrinkage compensation in the pressure holding stage, so that the green body product has a larger density, a larger unit weight, and a higher dimensional accuracy of the formed product. Filling the mold under a larger injection pressure can obtain a uniform filling effect and reduce the residual stress of the product. Because when the injection pressure increases, the polymer melt can fill the cavity in a shorter time, and the melt has sufficient relaxation time before solidification, thereby reducing the residual stress inside the product. The present invention obtains a good injection blank by adjusting important uPIM injection parameters such as injection temperature, injection pressure and mold temperature, thereby preventing defects such as blistering, cracks and pores from occurring on the product surface.
[0023] The degreasing process is the most time-consuming and difficult to control link, including several different stages, each stage can only remove one or several components in the binder; the purpose of staged degreasing is to maintain the shape of the green body and avoid collapse. In terms of process and cost, the degreasing time should be as short as possible to prevent defects or deformation of the green body, and to control the carbon and oxygen content. At present, there are three main degreasing methods: solvent degreasing, thermal degreasing and catalytic degreasing. After fully analyzing the advantages and disadvantages of existing binders and degreasing methods, the present invention determines to use polyacrylonitrile with better fluidity as a filler, high-density polyethylene and ethylene-vinyl acetate copolymer as skeleton materials to provide sufficient strength for the green body. In order to avoid the increase in carbon content caused by solvent degreasing, a one-step degreasing method of thermal degreasing is used to remove the binder, and the corresponding heating rate and holding time are effectively controlled to control the oxygen increment within the minimum range, while ensuring that the organic binder is removed cleanly to avoid the residual organic binder from forming carbides during the sintering process, causing an increase in carbon content. Compared with the traditional degreasing process, the production efficiency is improved by about , and the carbon content can be controlled within 800ppm, which is comparable to the performance of cast titanium alloy.
[0024] Sintering is a very important process in the uPIM process, and plays a decisive role in the organization, density and chemical uniformity of the product. The sintering of titanium alloy is generally solid phase sintering, and its main mass transfer mode is evaporation-condensation mass transfer and diffusion mass transfer. Compared with liquid phase sintering, its densification is more difficult. The diffusion of atoms is often accelerated by increasing the sintering temperature to increase the relative density of the product, but it is difficult to prevent the growth of grains. At the same time, the specific surface area of the small-sized particles used in uPIM is larger than that of the conventional PIM large-particle powder, and the driving force during sintering is large. The use of the same sintering temperature will cause the grain growth behavior to be more prominent. Therefore, the present invention adopts the method of pressure sintering, hot isostatic pressing sintering or plasma discharge sintering. At a sintering temperature lower than the usual sintering temperature of the powder, the grains will not aggregate and grow, and high pressure is applied to the titanium alloy powder, so that the powder particles are deformed, the actual contact area of the powder is increased, the atomic migration distance is shortened, and the densification is completed more quickly, so as to obtain a product with a fine crystal structure. Therefore, by applying these sintering processes, titanium alloy products can achieve 100% density, and have good microstructures such as fine grains, uniform organization, and no segregation of components. Then, by controlling the heating rate and holding time, the green body can be prevented from deformation, cracking and other defects during the sintering process.
[0025] Compared with the prior art, the present invention, based on the powder micro-injection molding technology, adopts the powder grading technology combined with the high fluidity binder system to prepare micron-grade titanium alloy parts with high dimensional accuracy and excellent mechanical properties, and its characteristics are as follows:
[0026] 1) High density and excellent product performance, comparable to the performance of cast titanium alloy;
[0027] 2) New binder system with low impurity content;
[0028] 3) One-step degreasing method, high production efficiency, easy to achieve mass production;
[0029] In summary, based on the powder microinjection molding technology, the present invention proposes the powder grading technology and high-fluidity binder system for the first time, and simultaneously optimizes the injection, degreasing and sintering process parameters involved in uPIM, which greatly reduces the carbon and oxygen impurity contents, and obtains micron-grade titanium alloy parts with performance comparable to that of cast titanium alloys. It has the advantages of high dimensional accuracy, low production cost, and easy mass production, and can well meet commercial needs. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram of titanium alloy products. DETAILED DESCRIPTION
[0031] The method of the present invention is further described below in conjunction with three embodiments.
[0032] Embodiment 1:
[0033] A method for preparing a micron-grade titanium alloy product, the process of which is as follows:
[0034] A. Raw material preparation: Titanium alloy powder is prepared by inert gas atomization method, which is a mixture of coarse powder and fine powder. The average particle size of the coarse powder is 25um, the average particle size of the fine powder is 3um, and the mass percentage of the fine powder is 10%.
[0035] B. Preparation of a binder: According to mass percentage, 68% polyacrylonitrile, 12% ethylene-vinyl acetate copolymer, 17% high-density polyethylene, and 3% stearic acid are used to prepare a binder;
[0036] C. Prepare feed: Mix the binder and titanium alloy material in a volume ratio of 32%:68%, granulate to prepare feed, mix at 180°C, mix at 90r / min, and mix for 4h;
[0037] D. Injection molding: Use a micro injection molding machine to inject the feed into the mold cavity to obtain a green product; the injection temperature is 160°C, the injection pressure is 110MPa, and the mold temperature is 60°C;
[0038] E. Debinding: The green body is thermally debinded in a vacuum debinding furnace. In an argon atmosphere, it is first heated to 350°C at a heating rate of 2°C / min and kept at that temperature for 1 hour. Then, it is heated to 500°C at a heating rate of 1°C / min and kept at that temperature for 2 hours. Then, it is cooled to room temperature along with the furnace.
[0039] F. Sintering: Sinter the degreased product body in a pressurized furnace; the vacuum degree in the furnace is 5*10-3Pa before filling with argon, then heat up and fill with argon, the sintering pressure is 300MPa (provided by argon), heat to 900℃ at a heating rate of 10℃ / min, keep warm for 1h, and cool to room temperature with the furnace to obtain the finished product.
[0040] G. Performance test: the oxygen content of the obtained titanium alloy product is 0.23wt.%, the tensile strength is 845MPa, the yield strength is 770MPa, the elongation is 8%, and the dimensional accuracy is ±0.35%.
[0041] Embodiment 2:
[0042] A method for preparing a micron-grade titanium alloy product, the process of which is as follows:
[0043] A. Raw material preparation: Titanium alloy powder is prepared by plasma beam rotating electrode atomization method, and is a mixture of coarse powder and fine powder. The average particle size of the coarse powder is 20um, the average particle size of the fine powder is 4um, and the mass percentage of the fine powder is 15%.
[0044] B. Preparation of a binder: According to mass percentage, 69% of polyacrylonitrile, 13% of ethylene-vinyl acetate copolymer, 15% of high-density polyethylene, and 3% of stearic acid are used to prepare a binder;
[0045] C. Prepare feed: Mix the binder and titanium alloy material in a volume ratio of 32%:68%, granulate to prepare feed, mix at 180°C, mix at 90r / min, and mix for 4h;
[0046] D. Injection molding: Use a micro injection molding machine to inject the feed into the mold cavity to obtain a green product; the injection temperature is 160°C, the injection pressure is 120MPa, and the mold temperature is 60°C;
[0047] E. Debinding: The green body is thermally debinded in a vacuum debinding furnace. In an argon atmosphere, it is first heated to 350°C at a heating rate of 2°C / min and kept at that temperature for 1 hour. Then, it is heated to 500°C at a heating rate of 1°C / min and kept at that temperature for 2 hours. Then, it is cooled to room temperature along with the furnace.
[0048] F. Sintering: Sinter the degreased product body in a hot isostatic pressing furnace; the vacuum degree in the furnace is 5*10-3Pa before filling with argon, then heat up and fill with argon, the sintering pressure is 200MPa (provided by argon), heat to 900℃ at a heating rate of 300℃ / min, keep warm for 0.5h, and cool to room temperature with the furnace to obtain the finished product.
[0049] G. Performance test: the oxygen content of the obtained titanium alloy product is 0.20wt.%, the tensile strength is 862MPa, the yield strength is 777MPa, the elongation is 9%, and the dimensional accuracy is ±0.35%.
[0050] Embodiment 3:
[0051] A method for preparing a micron-grade titanium alloy product, the process of which is as follows:
[0052] A. Raw material preparation: Titanium alloy powder is prepared by electrode induction melting gas atomization method, which is a mixture of coarse powder and fine powder. The average particle size of the coarse powder is 30um, the average particle size of the fine powder is 3um, and the mass percentage of the fine powder is 20%.
[0053] B. Preparation of a binder: According to mass percentage, 70% polyacrylonitrile, 15% ethylene-vinyl acetate copolymer, 13% high-density polyethylene, and 2% stearic acid are used to prepare a binder;
[0054] C. Prepare feed: Mix the binder and titanium alloy material in a volume ratio of 32%:68%, granulate to prepare feed, mix at 180°C, mix at 90r / min, and mix for 4h;
[0055] D. Injection molding: Use a micro injection molding machine to inject the feed into the mold cavity to obtain a green product; the injection temperature is 170°C, the injection pressure is 150MPa, and the mold temperature is 60°C;
[0056] E. Debinding: The green body is thermally debinded in a vacuum debinding furnace. In an argon atmosphere, it is first heated to 350°C at a heating rate of 2°C / min and kept at that temperature for 1 hour. Then, it is heated to 500°C at a heating rate of 1°C / min and kept at that temperature for 2 hours. Then, it is cooled to room temperature along with the furnace.
[0057] F. Sintering: Sinter the degreased product body in a discharge plasma furnace; the vacuum degree in the furnace is 5*10-3Pa before filling with argon, then heat up and fill with argon, the sintering pressure is 100MPa (provided by argon), heat to 800℃ at a heating rate of 300℃ / min, keep warm for 20min, and cool to room temperature with the furnace to obtain the finished product.
[0058] G. Performance test: the oxygen content of the obtained titanium alloy product is 0.20wt.%, the tensile strength is 878MPa, the yield strength is 789MPa, the elongation is 10%, and the dimensional accuracy is ±0.35%.
[0059] Comparative Example 1-1:
[0060] This comparative example adopts a method substantially the same as that of Example 3, except that the titanium alloy powder only comprises coarse powder, and the dimensional accuracy of the obtained titanium alloy product is ±0.7%, and the surface quality is poor.
[0061] Comparative Example 1-2:
[0062] This comparative example adopts a method basically the same as Example 3, except that the titanium alloy powder only contains fine powder, and the oxygen content of the obtained titanium alloy product reaches 0.62wt.%, the tensile strength is 825MPa, the yield strength is 733MPa, the elongation is 2%, and the mechanical properties are greatly reduced due to the excessively high oxygen content.
[0063] Comparative Examples 1-3:
[0064] This comparative example adopts a method basically the same as Example 3, except that the mass ratio of fine powder in the titanium alloy powder is 40%, and the oxygen content of the obtained titanium alloy product reaches 0.4wt.%, the tensile strength is 834MPa, the yield strength is 745MPa, the elongation is 4%, and the mechanical properties are reduced due to the high oxygen content.
[0065] Comparative Example 2-1:
[0066] This comparative example adopts the same method as Example 3, except that the binder is prepared according to the following mass percentages: 85% polyacrylonitrile, 8% ethylene-vinyl acetate copolymer, 5% high-density polyethylene, and 2% stearic acid. It is found that the feed fluidity is too good, the strength is insufficient, and it is deformed after sintering.
[0067] Comparative Example 2-2:
[0068] This comparative example adopts the same method as Example 3, except that the binder is prepared according to the following mass percentages: 55% polyacrylonitrile, 22% ethylene-vinyl acetate copolymer, 22% high-density polyethylene, and 1% stearic acid. It is found that the feed strength is high, but the fluidity is poor, and the yield is less than 30%.
[0069] Comparative Example 3-1
[0070] This comparative example adopts a method basically the same as that of Example 3, except that the green body of the product is first degreased by using a dichloromethane solvent for 4 hours at a temperature of 45°C. The carbon content of the obtained titanium alloy product reaches 0.2wt.%, and the elongation is only 2.5%.
[0071] Comparative Example 3-2
[0072] This comparative example adopts the same method as Example 3, except that it adopts a normal pressure sintering process, and the specific steps are: sintering the degreased product body in a vacuum sintering furnace; the vacuum degree in the furnace is 5*10-3Pa, heating to 1250℃ at a rate of 5℃ / min, keeping the temperature for 4h, and then cooling to room temperature with the furnace. The performance is tested, and the oxygen content of the obtained titanium alloy product reaches 0.35wt.%, the tensile strength is 855MPa, the yield strength is 756MPa, the elongation is 5%, and the mechanical properties are reduced due to the high oxygen content and grain size.
[0073] The above-described examples are only preferred implementation methods of the present invention, and therefore cannot be used to limit the scope of implementation of the present invention. Other equivalent changes, modifications, substitutions and combinations made in accordance with the principles and contents of the present invention still fall within the protection scope of the present invention.
Claims
1. A method for preparing a micron-grade titanium alloy product, characterized in that: The following steps are involved: First, titanium alloy powder is mixed with a binder and granulated to obtain feedstock; then a green body is obtained in a microinjection molding machine; finally, the green body is thermally degreased and sintered to obtain a titanium alloy product; The titanium alloy powder is a mixture of coarse powder and fine powder, the average particle size of the coarse powder is 15-30um, the average particle size of the fine powder is 2-5um, and the mass percentage of the fine powder is 10-20%; The grade of the titanium alloy powder is any one of TC4, TC9, TC11 and TC21; The binder is composed of the following components by mass percentage: 65-75% polyacrylonitrile, 10-20% ethylene-vinyl acetate copolymer, 10-20% high-density polyethylene, and 1-5% stearic acid; The sintering process is any one of pressure sintering, hot isostatic pressing sintering and plasma discharge sintering.
2. The method for preparing a micron-grade titanium alloy product according to claim 1, characterized in that: The titanium alloy powder is prepared by one of inert gas atomization, plasma beam rotating electrode atomization and electrode induction melting gas atomization.
3. The method for preparing a micron-grade titanium alloy product according to claim 1, characterized in that: During the mixing, the mixing temperature is 150-200° C., the mixing time is 1-4 hours, and the mixer speed is 80-120 r / min.
4. The method for preparing a micron-grade titanium alloy product according to claim 1, characterized in that: In the feed material, the volume ratio of binder to powder is 30-40% to 60-70%.
5. The method for preparing a micron-grade titanium alloy product according to claim 1, characterized in that: During the injection, the injection temperature is 150-180°C, the injection pressure is 90-150 MPa, and the mold temperature is 40-60°C.
6. The method for preparing a micron-grade titanium alloy product according to claim 1, characterized in that: The thermal degreasing process is: under the protection of argon atmosphere, first heating to 300-450°C at a heating rate of 1-3°C / min and keeping warm for 1-4h, then heating to 500-600°C at a heating rate of 1-3°C / min and keeping warm for 1-4h, and then cooling to room temperature with the furnace.
7. The method for preparing a micron-grade titanium alloy product according to claim 1, characterized in that: The protective atmosphere of the pressure sintering is argon, the sintering temperature is 800-1000°C, the holding time is 1-2h, the holding pressure is 100-300MPa, and the heating rate is 10-20°C / min; the protective atmosphere of the hot isostatic pressing sintering is argon, the sintering temperature is 900-1000°C, the holding time is 0.5-1h, the holding pressure is 100-300MPa, and the heating rate is 100-300°C / min; the protective atmosphere of the plasma discharge sintering is argon, the sintering temperature is 800-900°C, the holding time is 20-40min, the holding pressure is 50-150MPa, and the heating rate is 100-300°C / min.
8. The method for preparing a micron-grade titanium alloy product according to claim 1, characterized in that: The maximum size of the titanium alloy product is 500um.
9. The method for preparing a micron-grade titanium alloy product according to any one of claims 1 to 8, characterized in that: The obtained titanium alloy product has an oxygen content of no more than 0.25wt.%, a tensile strength of no less than 835MPa, a yield strength of no less than 765MPa, an elongation of no less than 5%, and a dimensional accuracy of ±0.3-0.5%.
Citation Information
Patent Citations
Powder micro injection molding method for ceramic substrate of printing head
CN101691086A
Preparation and application methods of thermoplastic adhesive for powder microinjection molding
CN102775673A
Water-soluble adhesive used for powder micro-injection shaping and preparation method thereof
CN106589562A
Method for preparing molybdenum and molybdenum alloys effuser by powder injection forming
CN101254537A
Ti-6Al-4V alloy feed for powder injection molding and preparation method of Ti-6Al-4V alloy feed
CN108326282A